VISUALIZATION OF COURAGE THE WIRONINI’S SOLDIERS IN THE FORM DRAMATIC DANCE ON DANCE WORK “KRIDHAH SANG ABITHAH” - Arsyika, Aulia Nanda; Sasanadjati, Jajuk Dwi (Solah, 2025)
The dance work 'Kridhah Sang Abithah' is a work that carries the theme of the phenomenon of courage which is also the choreographer's empirical experience. This phenomenon was taken from the courage possessed by Wironini soldiers in fighting the allies, defending Untung Suropati in defending the land of Pasuruan. The choreographer was interested in the phenomenon of bravery of the Wironini soldiers because it is related to the phenomenon experienced by women today. The focus of the form in this work is a type of dramatic dance which is a reinforcement in depicting the atmosphere and the focus of the content is the visualization of the courage of the female soldier 'Wironini'. The aim of creating this dance work is to visualize the courage of the Wironini Pasuruan soldiers and convey the message contained in it through the dancers' body movement expressions. The choreographer uses choreography theory by Sumandiyo Hadi and construction method theory I by Jacqluine Smith to support the analysis of his dance creation. This dance work is also supported by various elements, such as movement, music, make-up, clothing, props and lighting that match the dance theme. The flow of the content in the dance work 'Kridhah Sang Abithah' consists of an opening, 5 main scenes and an ending. Danced by 9 dancers and supported by 24 movement motifs and floor patterns. The message conveyed by this dance work is that a woman must also have courage and firmness in making decisions when acting.